Fabrication of Silver Nanoparticles Decorated on Activated Screen Printed Carbon Electrode and Its Application for Ultrasensitive Detection of Dopamine. Issue 8 (12th June 2015) - Palanisamy, Selvakumar; Thirumalraj, Balamurugan; Chen, Shen‐Ming; Ajmal Ali, M.; Muthupandi, K.; Emmanuel, R.; Prakash, P.; Al‐Hemaid, Fahad M. A.
Abstract In the present study, we report the fabrication of silver nanoparticles (AgNPs) decorated on activated screen printed carbon electrode (ASPCE). The AgNPs were prepared by using Justicia glauca leaf extract as a reducing and stabilizing agent and the ASPCE was prepared by a simple electrochemical activation of screen printed carbon electrode (SPCE). The ASPCE/AgNPs shows a reversible electrochemical behaviour with enhanced response for DA than that of other modified SPCEs. Under optimum conditions, the electrochemical oxidation current response of DA is linear over the concentration range from 0.05 to 45.35 µM. The limit of detection is found as 0.017 µM with a high sensitivity of 7.85 µA µM−1 cm−2.